From Miracle to Market: Commodifying Iʿjāz al-Qurʾān on Indonesian TikTok - Nabrisatul Chusna Bil-Makkiy; Miski Miski (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines TikTok content in Indonesia featuring the “Keajaiban Al-Quran (Miracles of the Qur’an),” focusing on its intersection with product promotion and audience engagement, which reflects practices of religious commodification. It investigates the relationship between posts highlighting Qur’anic miracles and broader Qur’anic scholarship, identifying strategies of commodification and their impact on audience perceptions of the Qur’anic concepts presented. Using Miles and Huberman’s content analysis framework—data reduction, display, and conclusion drawing—the study finds three key points. First, TikTok posts contribute to the popularization and construction of the concept of iʿjāz al-Qurʾān. Second, the presentation of this concept is closely tied to commodification through product promotion, engagement prompts (likes, shares, comments, follows), and hashtags. Third, audiences generally accept and actively disseminate these commodified posts. TikTok features, including the “yellow basket” and audiovisual framing, enhance engagement and perceived credibility. However, these posts risk misrepresenting iʿjāz al-Qurʾān and weakening viewers’ critical reasoning. The study highlights how social media dissemination of Qur’anic knowledge is increasingly susceptible to distortion, shaped by competing personal and group interests.